Geologi Daerah Geothermal Pangi Kabupaten Bone Bolango Provinsi Gorontalo - Dewi Darmayanti Tolodo; Fauzul Chaidir A. Usman; Intan Noviantari Manyoe; Fitra Akbar Gaib; Fitri Handayani Putje; Yusran Ibrahim (Jambura Geoscience Review, 2019)
Geothermal is associated with volcanic that still has heat energy below the surface. Indonesia is a country with geothermal energy reserves of around 40%. There are 256 potential geothermal areas and only 7 locations have been utilized. Gorontalo has several geothermal manifestations, such as Lombongo, Pangi, Libungo, and Hungayono. The purpose of this study was to study the geology of the geothermal manifestations of Pangi, East Suwawa District, Bone Bolango Regency, Gorontalo Province. The research method is divided into field observations, laboratory analysis, and studio analysis. The results of this research show that the geomorphology in the study area is divided into 3 units, namely the Fluvial Plain, the Volcanic Hills, and the Structural Use Landscape. Alluvial Deposition Unit, Volcanic Breccia Unit, Tuff Lapili Unit, Andesite Unit, Granodiorite Unit, and Porphyry Diorite Unit.